A DESCRIPTIVE STUDY ON THE IMPROVEMENT OF STUDENTS’ READING COMPREHENSION THROUGH NUMBER HEAD TOGETHER TECHNIQUE - Tri Rohani; Vera Yuniar; Yuliana Yuliana (STKIP PGRI Situbondo, 2022)
This research aims to describe the improvement of students reading comprehension by using Number Head Together (NHT) technique from ten (10) articles selected. This research used qualitative method and descriptive analysis. The results of this research found that from the ten (10) articles analyzed, A10 was the most improved article in reading comprehension by using Number Head Together technique compare to other nine (9) articles. Futhermore, based on the t-test result of the use of NHT technique in reading comprehension, the result reveals that from nine (9) articles, 90% which used NHT in the teaching process proved that the achievement were more improved, while one (1) of the articles (10%) did not mention the t-test result but confirmed that there was improvement in the results of students’ reading comprehension .This indicates that Number Head Together (NHT) technique improved students’ reading comprehension. Number Head Together (NHT) technique not only results on students interest in learning process but also involved the students in the activity of collaborative learning as team or group. However, this grouping motivated the students to produce better achievement in their study activity.